Umbilical cord blood banking and transplantation - Ballen, Karen (Stem Cell Biology and Regenerative Medicine, 2014)
This comprehensive volume discusses the current scope of umbilical cord blood transplantation (UCBT), including recent controversies and future developments for improving clinical outcomes. Its twenty chapters introduce new applications in regenerative medicine and discuss the latest scientific, regulatory, clinical and investigational aspects of cord blood banking. Physicians from around the world provide a global collaboration which explores strategies for umbilical cord blood expansion, homing, unit selection, and combining of graft sources to improve patient outcomes. Umbilical Cord Blood Banking and Transplantation also reviews advances in pediatric UCBT for hematologic and non-hematologic disorders as well as immune recovery, which is critical to preventing infection. Finally, it compares UCBT with other graft sources in an attempt to understand the optimal graft source for the individual patient. UCBT is an important option for many patients who need a transplant but do not have a family donor or a matched unrelated donor. The collective and timely  knowledge presented here is essential reading for any regenerative medicine investigator, cord blood banker, transplant laboratory scientist or clinical physician interested in improving and expanding the applications of umbilical cord blood.